Launching A Ready Meals Production and Delivery Project in Russia: Prospects and Problems - Elena DOROKHINA; Elena SMIRNOVA (Communications of International Proceedings, 2022)
The Covid-19 pandemic and the quarantine measures associated with it significantly increased demand for the delivery of ready-made meals. Current political situation forced many global players leave the Russian market and “opened the door” for the local players. Lack of finance and expertise make them choose franchising as an adequate business model.  These factors jointly make the prospects of launching the project that the authors consider very optimistic. The authors present their analysis of the state of the ready meals market in Russia; consider the idea, advantages and limitations of the project, the project management methodology to apply, the lines along which the project will develop. The risks associated with the project are identified and quantitatively estimated
Keywords: ready meals; project launch; project management; risk management.